Linguistic Sign on The Name of The Carvings of Rumah Gadang in Sungai Beringin Payakumbuh: Semiotic Analysis - Mac Aditiawarman; Indri Dwi Avinta (Jurnal Ilmiah Pendidikan Scholastic, 2023)
The research discusses the linguistic sign on the name of the carvings of Rumah Gadang in Sungai Beringin Payakumbuh. The names of the carvings were found based on interviews and direct observations made with the owner of the Sanggar ukir in the village of Nunang Payakumbuh Barat. This research aims to find out the signifier and signified contained in the carvings of the name of the Rumah Gadang. In addition, this research also analyzed the meaning of the name carvings of the Rumah Gadang. The theory used in this research is semiotics, which refers to Chandler theory of linguistic signs. This research was conducted using qualitative descriptive research. The results of the research found that 26 carvings of the name Rumah Gadang Sungai Beringin came from natural patterns and were related to the natural philosophy espoused by the Minangkabau people. In conclusion, carvings are analyzed from signifier and signified, the denotation and connotation meaning and cultural meanings contained in the name of the carvings of the Rumah Gadang.